Confluência entre tradição e ciência: construção e socialização de conhecimentos sobre racismo ambiental na reserva indígena Taba dos Anacé - Martins, Iara Saraiva (2025)
This thesis analyzes the process of constructing and sharing knowledge on environmental racism in the Taba dos Anacé Indigenous Reserve, located in the Metropolitan Region of Fortaleza, Ceará. The study aims to understand the articulation between traditional and academic knowledge in addressing the environmental injustices experienced by Indigenous peoples, focusing on the Anacé territory and the socio-environmental impacts of the Pecém Industrial and Port Complex (CIPP). The methodology used was action research with a qualitative and participatory approach, integrating Indigenous epistemologies and practices of environmental and territorial resistance. Theoretical contributions from Aníbal Quijano (2005), Achille Mbembe(2018), Linda Tuhiwai Smith (2018), and Joan Martínez Alier (2016) informed the discussions presented. The thesis is structured in seven chapters, discussing the impact of capitalism on Indigenous territoriality and the reconfigurations of coloniality. It also examines the relationship between structural racism, necropolitics, and environmental injustice, as well as issues related to genocide, epistemicide, and ecocide. The results highlight participant observation activities and workshops conducted with leaders of theTaba dos Anacé Indigenous Reserve, where the integration of academic concepts and traditional knowledge contributed to the operationalization of the concept of environmental racism. The research reveals that decolonial education and theappreciation of local knowledge are essential to strengthening Indigenous autonomy and resistance.